2021
DOI: 10.3390/brainsci11091196
|View full text |Cite
|
Sign up to set email alerts
|

Differential Influence of the Dorsal Premotor and Primary Somatosensory Cortex on Corticospinal Excitability during Kinesthetic and Visual Motor Imagery: A Low-Frequency Repetitive Transcranial Magnetic Stimulation Study

Abstract: Consistent evidence suggests that motor imagery involves the activation of several sensorimotor areas also involved during action execution, including the dorsal premotor cortex (dPMC) and the primary somatosensory cortex (S1). However, it is still unclear whether their involvement is specific for either kinesthetic or visual imagery or whether they contribute to motor activation for both modalities. Although sensorial experience during motor imagery is often multimodal, identifying the modality exerting great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 83 publications
0
7
0
Order By: Relevance
“…Although this remains speculative, the facilitatory input from PMd to M1 during MI has decreased the SICI level within M1. Moreover, the opposite higher level of SICI during MI (vs. rest) observed with PA current reflect the activation of inhibitory inputs received from the somatosensory cortex and the supplementary motor area, both areas known to functionally inhibit M1 when imagining (Kasess et al, 2008; Oldrati et al, 2021). Finally, it is also possible that the cerebellum, which facilitates M1 excitability during MI (Rannaud Monany et al, 2022; Tanaka et al, 2018), also contributes to the result of the current study because the influence of the cerebellum on M1 might occur via interactions with specific I‐waves generating circuits (Spampinato et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this remains speculative, the facilitatory input from PMd to M1 during MI has decreased the SICI level within M1. Moreover, the opposite higher level of SICI during MI (vs. rest) observed with PA current reflect the activation of inhibitory inputs received from the somatosensory cortex and the supplementary motor area, both areas known to functionally inhibit M1 when imagining (Kasess et al, 2008; Oldrati et al, 2021). Finally, it is also possible that the cerebellum, which facilitates M1 excitability during MI (Rannaud Monany et al, 2022; Tanaka et al, 2018), also contributes to the result of the current study because the influence of the cerebellum on M1 might occur via interactions with specific I‐waves generating circuits (Spampinato et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…For example, late I‐waves evoked by AP orientation could activate axons of neurons of the premotor cortex projecting to the corticospinal cells (Aberra et al, 2020; Desmons et al, 2021; Groppa et al, 2012; Siebner, 2020; Volz et al, 2015). Recently, Oldrati et al (2021) reported that following off‐line 1‐Hz inhibitory repetitive TMS over the dorsal premotor cortex (PMd), corticospinal excitability assessed during kinesthetic MI was not significantly higher than rest condition (Oldrati et al, 2021). These findings suggest facilitatory connectivity from PMd to M1 during MI.…”
Section: Discussionmentioning
confidence: 99%
“…For example, late I-waves evoked by AP orientation could activate axons of neurons of the premotor cortex projecting to the corticospinal cells (Groppa et al ., 2012; Volz et al ., 2015; Aberra et al ., 2020; Siebner, 2020; Desmons et al ., 2021). Recently, Oldrati et al (2021) reported that following offline 1Hz inhibitory repetitive TMS over the dorsal premotor cortex (PMd), corticospinal excitability assessed during kinesthetic MI was not significantly higher than rest condition (Oldrati et al ., 2021). These findings suggest a facilitatory connectivity from PMd to M1 during MI.…”
Section: Discussionmentioning
confidence: 99%
“…Although this remains speculative, it is possible that the facilitatory input from PMd to M1 occurring during MI has decreased the SICI level within M1. Moreover, the opposite higher level of SICI during MI (vs. rest) observed with PA current reflect the activation of inhibitory inputs received from somatosensory cortex and SMA, both areas known to functionally inhibit M1 when imagining (Kasess et al ., 2008; Oldrati et al ., 2021). Finally, it is also possible that cerebellum, which facilitates M1 excitability during MI (Tanaka et al ., 2018; Monany et al ., 2021), also contributes to the result of the current study since the influence of cerebellum on M1 might occur via interactions with specific I-waves generating circuits (Spampinato et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that the SMA contributes to MI by coordinating and planning motor sequences. Furthermore, TMS studies have revealed that stimulating the dorsal premotor cortex (PMd) during MI tasks can modulate corticospinal excitability [ 42 , 43 ]. This shows that the PMd is involved in motor planning and execution processes during MI.…”
Section: Introductionmentioning
confidence: 99%